Character education for environmental awareness through introducing zero waste management to young children - Rosi Tunas Karomah (Journal of Character and Environment, 2026)
Background: The widespread waste phenomenon in Indonesia has caused other environmental damage, such as contaminated clean water sourcer, flooding that damages buildings and infrastructure, and even claims lives. This is due to a lack of public awareness of the environment and suboptimal waste management. The aims of this research is to provide education and understanding of environmental care character in children by introducing zero waste management. Methods: The qualitative research used a case study method at ABA Kindegarten Ambarawa. The subjects were the 1 class teacher and 15 students in class A. data were collected through observation, interviews, and documentation. Data analysis was carried out through data reduction, presesntation, and verification. Findings: Educators can develop a caring character for the environment by introducing zero waste management to early childhood. Educational activities have been implemented to instill a caring character for the environment, including introducing young children to various types of waste, instilling the habit of disposing of waste properly, introducing and teaching the management of organic waste into compost, and utilizing recycled plastic waste as a learning medium and creative work for young children. These activities are expectied to instill and foster a habit of caring for the environment. By becoming accustomed to healthy and clean living from a young age, childreen will maintain a healthy environment. Conclusion: Environmentally conscious behavior can begin with the instilling of healthy lifestyle habits in young children. Introducing waste management through recycling and composting. Novelty/Originality of this article: The research discusses three things in waste management, namely habituation, recycling and composting. Few studies discuss these three thing in one article.